Pengaruh media pembelajaran berbasis komputer terhadap hasil belajar IPA ditinjau dari motivasi belajar siswa - Ika Soimah (Universitas Sarjanawiyata Tamansiswa, 2018)
This study was aimed to find out the significane difference between the students’ learning outcomes that were taught by using computer- based media and a conventional method in terms of students’ motivation of the seventh grade students of SMP Negeri 4 Gringsing Batang in 2016/2017 academic year. This study was a quasi experimental study. Two of four classes were taken as the sample group. The data were gained through tests. To analyzee the data, this study employed a One-Way ANAKOVA test. The result revealed that the mean value the students that were taught by using computer-based media was 23,429 and those that were taught by using a conventional method in terms of students’ motivation was 17,517. In conclusion, there is a significance difference between the students’ learning outcomes that were taught by using computer-based media and a conventional method in terms of students’ motivation.